Surface-coated sulfide solid electrolyte as well as preparation method and application thereof
By coating nano-alumina, lithium titanium phosphate or lithium phosphate on the surface of the sulfide solid electrolyte, the air stability problem of the sulfide solid electrolyte is solved, and a high ionic conductivity and low-cost processing technology is achieved, which is suitable for all-solid lithium batteries.
Patent Information
- Application Number
- CN202510530163.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-01
AI Technical Summary
The existing sulfide solid electrolytes have poor air stability, which affects the process and application and is costly.
By mixing the sulfide solid electrolyte with nanoparticles with oxygen-containing functional groups and vacuum drying, a surface-covered sulfide solid electrolyte is formed, and the coating material is nanoalumina, nanolithium titanium phosphate or nanolithium phosphate.
It improves the air stability performance of sulfide solid electrolytes, maintains high ionic conductivity, simplifies processing technology, reduces costs, and is especially effective for nano-scale particles.
Smart Images

Figure CN120413768A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy battery materials, and particularly relates to a surface-coated sulfide solid electrolyte, a preparation method thereof, and an application thereof. Background Art
[0002] All-solid-state lithium batteries are considered to be the next-generation battery technology with great application prospects due to their extremely high safety and higher energy density. Currently, the key to the development of all-solid-state lithium batteries lies in preparing solid electrolytes with low cost and high lithium ion conductivity, while solving problems such as poor electrode / electrolyte interface compatibility and lithium dendrite growth. The solid electrolyte is the core part of the all-solid-state lithium battery, so it is also one of the key research points of the all-solid-state lithium battery. Compared with other solid electrolytes, sulfide solid electrolytes have excellent lithium ion conductivity, mechanical properties that are easy to process and form, and good interface stability between the electrode and the electrolyte, making them the most promising solid electrolytes. However, from the perspective of all-solid-state lithium batteries that meet high energy density, high power density, and high safety performance, the ionic conductivity of most current sulfide solid electrolytes still cannot meet these requirements, especially the air stability problem. The air stability problem of sulfides has a great impact on both the manufacturing process and the application, greatly increasing the manufacturing, storage, and transportation costs.
[0003] Therefore, the existing technology still needs to be improved and developed. Summary of the Invention
[0004] In view of the above deficiencies of the prior art, the purpose of the present invention is to provide a surface-coated sulfide solid electrolyte, a preparation method thereof, and an application thereof, aiming to solve the problem of poor air stability of existing sulfide solid electrolytes.
[0005] The technical solution of the present invention is as follows:
[0006] In the first aspect of the present invention, a preparation method of a surface-coated sulfide solid electrolyte is provided, including:
[0007] Step S1: Mix and stir the sulfide solid electrolyte and a first solvent to obtain a first mixed solution; mix and stir the nanoparticles with oxygen-containing functional groups and a second solvent to obtain a second mixed solution;
[0008] Step S2: Add the second mixed solution to the first mixed solution and stir to obtain a third mixed solution;
[0009] Step S3: Vacuum-dry the third mixed solution to obtain the surface-coated sulfide solid electrolyte.
[0010] Optionally, the nanoparticles with oxygen-containing functional groups are one or more of nano-aluminum oxide, lithium aluminum titanium phosphate nano-particles, and lithium phosphate nano-particles.
[0011] Optionally, the particle size of the sulfide solid electrolyte is 400 nm to 10 μm, and the size of the nanoparticles with oxygen-containing functional groups is 5 nm to 10 nm.
[0012] Optionally, the solid content of the first mixed solution is 10% to 50%, and the solid content of the second mixed solution is 10% to 50%.
[0013] Optionally, the first solvent and the second solvent are each independently selected from one or more of p-xylene, butyl acetate, and toluene.
[0014] Optionally, in step S2, the addition rate of the second mixed solution is 0.5 s / drop to 2 s / drop, and the addition amount of the second mixed solution is 0.25% to 2% of the mass of the first mixed solution.
[0015] Optionally, in step S2, the stirring speed is 200 r / min to 2000 r / min, and the stirring time is 5 min to 2 h.
[0016] Optionally, the temperature of the vacuum drying is 50°C to 200°C, and the time of the vacuum drying is 10 h to 24 h.
[0017] In the second aspect of the present invention, there is provided a surface-coated sulfide solid electrolyte prepared by the preparation method of the surface-coated sulfide solid electrolyte described in the present invention.
[0018] In the third aspect of the present invention, there is provided a all-solid-state lithium battery, including the surface-coated sulfide solid electrolyte described in the present invention.
[0019] Beneficial effects: The present invention realizes surface particle coating of the sulfide solid electrolyte through simple mixing and vacuum drying. The oxygen-containing functional groups are attached to the particle surface, making the material more oxygen-philic, improving the air stability of the sulfide solid electrolyte. The material still maintains a high ionic conductivity and has good electrochemical properties. And the present invention can achieve the purpose of improving air stability without stabilizing the coating layer through a high-temperature sintering process, reducing the processing technology, being more simplified and feasible for practical applications, and also greatly reducing the processing cost. In particular, it can also coat nano-scale sulfide solid electrolyte particles, which has more practical application value. Description of the Drawings
[0020] Figure 1 It is a flowchart of a preparation method of a surface-coated sulfide solid electrolyte provided by the present invention.
[0021] Figure 2 Schematic diagram of a preparation method of a surface-coated sulfide solid electrolyte provided for Example 1.
[0022] Figure 3 Electrochemical performance graph of a mold battery prepared with a sulfide solid electrolyte without surface coating.
[0023] Figure 4 Electrochemical performance graph of a mold battery prepared with the surface-coated sulfide solid electrolyte obtained in Example 1. Detailed implementation manners
[0024] The present invention provides a surface-coated sulfide solid electrolyte, a preparation method thereof and an application. To make the objectives, technical solutions and effects of the present invention clearer and more definite, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0025] As Figure 1 shown, an embodiment of the present invention provides a preparation method of a surface-coated sulfide solid electrolyte, which includes:
[0026] Step S1: Mix and stir a sulfide solid electrolyte and a first solvent to obtain a first mixed solution; mix and stir nanoparticles with oxygen-containing functional groups and a second solvent to obtain a second mixed solution;
[0027] Step S2: Add the second mixed solution to the first mixed solution and stir to obtain a third mixed solution;
[0028] Step S3: Vacuum-dry the third mixed solution to obtain the surface-coated sulfide solid electrolyte.
[0029] In an embodiment of the present invention, by simply mixing a sulfide solid electrolyte (LPSC) and nanoparticles with oxygen-containing functional groups and then performing vacuum drying, the surface-coated sulfide solid electrolyte can be obtained. The attachment of oxygen-containing functional groups on the particle surface makes the material more oxygen-philic, improving the air stability of the sulfide solid electrolyte. The material still maintains high ionic conductivity and has good electrochemical performance. Moreover, the present invention can achieve the purpose of improving air stability without the process of high-temperature sintering to stabilize the coating layer, reducing the processing process, being more simplified and feasible for practical applications, and greatly reducing the processing cost. In particular, it can coat nanoparticles of sulfide solid electrolytes, which has more practical application value.
[0030] In the embodiment of the present invention, the surface-coated sulfide solid electrolyte is prepared with the sulfide solid electrolyte LPSC as the core, and nanoparticles with oxygen-containing functional groups are used as the coating layer to coat the surface of the LPSC material.
[0031] In some embodiments, the nanoparticles with oxygen-containing functional groups are one or more of nano-aluminum oxide, lithium aluminum titanium phosphate nano, and lithium phosphate nano.
[0032] In this embodiment, the nano-aluminum oxide of the coating layer has the following advantages: First, it has a physical isolation effect. The dense structure of aluminum oxide can form a physical barrier to prevent gases such as moisture, oxygen, and CO2 from contacting the LPSC surface and inhibit the hydrolysis reaction. Second, it has a chemical passivation effect. The hydroxyl groups (-OH) on the surface of aluminum oxide can form hydrogen bonds with the sulfide groups on the LPSC surface, reducing the sulfur vacancy concentration and decreasing the oxygen molecule adsorption and oxidation reaction. Third, it improves anti-agglomeration and dispersibility. The surface charge and steric hindrance effects of nano-aluminum oxide can prevent LPSC particles from agglomerating, expand the effective contact area, and maintain the uniformity of the electrolyte membrane.
[0033] The lithium aluminum titanium phosphate nano (LATP) of the coating layer has the following advantages: First, it optimizes the interface compatibility. As an oxide solid electrolyte, LATP forms a bilayer structure with LPSC: the inner sulfide provides high ionic conductivity (>10 mS / cm), and the outer LATP enhances chemical stability. The lattice structure of LATP can match the LPSC interface and reduce cracks caused by lattice mismatch. Second, it inhibits oxygen vacancies. Al 3+ and P 5+ in LATP can neutralize the active oxygen vacancies on the LPSC surface and reduce the adsorption and oxidation reaction activity of oxygen molecules at the interface. Third, it broadens the electrochemical window. The oxidation potential of LATP is relatively high (>5V vs. Li / Li + ), which can prevent LPSC from decomposing at high voltages and improve the cycle stability of all-solid-state batteries.
[0034] The lithium phosphate nano of the coating layer has the following advantages: First, it neutralizes hygroscopicity. Li3PO4 reacts with trace moisture to generate LiOH and H3PO4, consuming the moisture in the environment and reducing the generation of LPSC hydrolysis products (such as Li3PO4), thereby reducing the electrolyte degradation rate. Second, it buffers acidic products. The basic property of lithium phosphate can neutralize the acidic gases (such as H2S) generated by LPSC hydrolysis and inhibit the corrosion of battery components by hydrogen sulfide. Third, it regulates the ion transport channels. The lithium ion conduction performance of Li3PO4 (about 10 -3 S / cm) can partially replace the ion transport path of LPSC and reduce the conductivity loss caused by coating.
[0035] In some embodiments, the particle size of the sulfide solid electrolyte is 400 nm to 10 μm (for example, it can be 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1 μm, 5 μm, 10 μm, etc.), and the particle size of the nanoparticles with oxygen-containing functional groups is 5 nm to 10 nm (for example, it can be 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, 10 nm, etc.). Generally speaking, there is a possibility of coating only when the size difference between the coated particles and the particles to be coated is more than a hundred times. In the present invention, the sulfide solid electrolyte with small particles having a size of 400 nm to 10 μm is coated by using nanoparticles with oxygen-containing functional groups having a size of 5 nm to 10 nm, improving the air stability of the small-particle sulfide solid electrolyte and having more practical application value.
[0036] In some embodiments, the solid content of the first mixed solution is 10% to 50% (for example, it can be 10%, 20%, 30%, 40%, 50%, etc.), and the solid content of the second mixed solution is 10% to 50% (for example, it can be 10%, 20%, 30%, 40%, 50%, etc.).
[0037] In some embodiments, the first solvent and the second solvent can be organic solvents such as aromatic hydrocarbon solvents and ester solvents, and specifically can be one or more of p-xylene, butyl acetate, and toluene.
[0038] In some embodiments, in step S1, the speed of the mixing and stirring is 200 r / min to 2000 r / min (for example, it can be 200 r / min, 500 r / min, 1000 r / min, 1500 r / min, 2000 r / min, etc.), and the time of the mixing and stirring is 5 min to 2 h (for example, it can be 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 1 h, 1.5 h, 2 h, etc.).
[0039] In some embodiments, in step S2, the addition rate of the second mixed solution is 0.5 s / drop to 2 s / drop (for example, it can be 0.5 s / drop, 1 s / drop, 1.5 s / drop, 2 s / drop, etc.), and the addition amount of the second mixed solution is 0.25% to 2% of the mass of the first mixed solution (for example, it can be 0.25%, 0.5%, 0.75%, 1%, 1.25%, 1.5%, 1.75%, 2%, etc.).
[0040] In some embodiments, in step S2, the stirring speed is 200 r / min to 2000 r / min (for example, it can be 200 r / min, 500 r / min, 1000 r / min, 1500 r / min, 2000 r / min, etc.), and the stirring time is 5 min to 2 h (for example, it can be 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 1 h, 1.5 h, 2 h, etc.).
[0041] In some embodiments, the temperature of the vacuum drying is 50°C to 200°C (for example, it can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.), and the time of the vacuum drying is 10 h to 24 h (for example, it can be 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, etc.). Vacuum drying is to prevent the organic solvent inside the material from not being baked out after heating during the drying process, or being re-adsorbed when the temperature drops. And drying within this temperature range is effective. If the temperature is lower than 50°C, the drying time is too long; if it is higher than 200°C, other side reactions may be introduced; the baking time is adjusted correspondingly according to the baking temperature. When the temperature increases, the baking time is shortened correspondingly to achieve the same effect.
[0042] The embodiment of the present invention also provides a surface-coated sulfide solid electrolyte prepared by using the preparation method of the surface-coated sulfide solid electrolyte described in any one of the foregoing embodiments. The surface-coated sulfide solid electrolyte prepared by the preparation method of the present invention improves the air stability of the sulfide solid electrolyte, still maintains a high ionic conductivity, and basically does not affect the charge-discharge capacity and initial efficiency of the material, and has good electrochemical performance.
[0043] The embodiment of the present invention also provides a all-solid-state lithium battery, which includes the surface-coated sulfide solid electrolyte described in the foregoing embodiment.
[0044] The present invention will be further described below through specific embodiments.
[0045] Example 1
[0046] This embodiment provides a preparation method of a surface-coated sulfide solid electrolyte, as Figure 2 shown, including the following steps:
[0047] Put the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5Put p-xylene into a magnetic stirring container, adjust the solid content to 30%, stir at a speed of 1000 r / min for 1 h to obtain the first mixed solution; mix nano-aluminum oxide and p-xylene, adjust the solid content to 30%, and stir to obtain the second mixed solution;
[0048] Gradually and slowly drop the second mixed solution into the first mixed solution at a dropping speed of 1 s / drop. The addition amount of the second mixed solution is 0.5% of the mass of the first mixed solution, and continuously stir magnetically at a speed of 1000 r / min for 1 h to obtain the third mixed solution;
[0049] Pour out the third mixed solution and place it in a vacuum oven at 160 °C for vacuum drying for 15 h to obtain a surface-coated sulfide solid electrolyte.
[0050] Performance test:
[0051] (1) Test the air stability of the surface-coated sulfide solid electrolyte (referred to as LPSC after coating) and the uncoated sulfide solid electrolyte (referred to as LPSC before coating) prepared in Example 1, specifically as follows:
[0052] Cold-press the LPSC before coating and the LPSC after coating into sheets at 400 Mpa respectively, with a thickness of 1 mm and a diameter of 10 mm to obtain two samples to be tested. Place the two samples to be tested in multiple portions in an air-stable experimental chamber with a humidity of 5%, and take out the corresponding samples to be tested at different time nodes (1 h, 3 h, 6 h, 9 h, 18 h) to test the ionic conductivity. The specific results are shown in Table 1.
[0053] The test method for ionic conductivity is as follows: Use a blocking electrode (such as stainless steel or sputtered metal film) to hold the sample to be tested, and apply an alternating voltage (amplitude 10 mV, frequency range 1 MHz - 0.1 Hz). Obtain the bulk resistance R bulk through EIS fitting of the high-frequency region semi-circle intercept. The low-frequency region reflects the interface resistance and double-layer effect. According to the formula calculate the ionic conductivity of the corresponding sample to be tested, where σ is the ionic conductivity, R bulk is the bulk resistance, L is the thickness of the sample to be tested, and A is the effective contact area of the sample to be tested.
[0054] Table 1
[0055] Sample to be measured Exposure time to air Ionic conductivity (mS / cm) LPSC before coating 0h 4.7 LPSC before coating 1h 4.3 LPSC before coating 3h 3.7 LPSC before coating 6h 1.6 LPSC before coating 9h 0.1 LPSC before coating 18h 0.08 LPSC after coating 0h 3.3 LPSC after coating 1h 3.2 LPSC after coating 3h 2.1 LPSC after coating 6h 1.5 LPSC after coating 9h 1.3 LPSC after coating 18h 0.9
[0056] As can be seen from the data in Table 1, as the exposure time of the sample in air increases, the ionic conductivity of the uncoated sulfide solid electrolyte drops rapidly. After 9 hours, it has dropped to near-insulating. However, for the surface-coated sulfide solid electrolyte prepared by the method of the present invention, the initial conductivity decreases slightly, but as the exposure time in air increases, the decrease amplitude is not large. Even at 18 hours, the ionic conductivity can still reach nearly 1 mS / cm. This shows that by performing surface particle coating on the sulfide solid electrolyte, the present invention can maintain the ionic conductivity of the material and improve the air stability of the sulfide solid electrolyte.
[0057] (2) Test the electrochemical properties of the surface-coated sulfide solid electrolyte (referred to as LPSC after coating) and the uncoated sulfide solid electrolyte (referred to as LPSC before coating) prepared in Example 1, specifically as follows:
[0058] Take the samples to be tested of LPSC before coating and LPSC after coating as electrolyte powder materials respectively, cold press them into sheets at 400 Mpa, with a thickness of 1 mm and a diameter of 10 mm, to ensure density (porosity ≤ 5%). Apply force evenly during pressing to avoid cracking or denting, which may affect the test results. Then apply a pressure of 300 Mpa to add the NCM811 positive electrode and the graphite negative electrode on both sides of the ceramic sheet respectively and press again. Combine the positive electrode NCM811 + the sample electrolyte material to be tested + graphite and apply a pressure of 4 Mpa to synthesize a mold battery, and put it into the battery cabinet for testing. The test procedure is a constant current charge and discharge at 0.1C, and observe the electrochemical properties of the mold battery.
[0059] Figure 3 It is the electrochemical performance diagram of the mold battery prepared with the uncoated sulfide solid electrolyte. Figure 4 It is the electrochemical performance diagram of the mold battery prepared with the surface-coated sulfide solid electrolyte prepared in Example 1. The specific data results are shown in Table 2 (where mold battery 1 is the mold battery prepared with LPSC before coating, and mold battery 2 is the mold battery prepared with LPSC after coating).
[0060] Table 2
[0061] Number Charge capacity (mAh / g) Discharge capacity (mAh / g) Initial efficiency (%) Mold battery 1 208.34 172.22 82.66 Mold battery 2 210.22 172.13 81.88
[0062] As can be seen from the data in Table 2, the charge and discharge capacities and the first efficiency of the mold batteries prepared with LPSC before coating and LPSC after coating are basically the same. This shows that after the sulfide solid electrolyte is coated with nanoparticles with oxygen-containing functional groups, it will not have an obvious impact on the charge and discharge and the first efficiency of the material itself. That is, the surface-coated sulfide solid electrolyte prepared by the method of the present invention can maintain good electrochemical properties.
[0063] In summary, the present invention realizes the surface particle coating of the sulfide solid electrolyte through simple mixing and vacuum drying. Oxygen-containing functional groups are attached to the particle surface, making the material more oxygen-philic, improving the air stability of the sulfide solid electrolyte. The material still maintains a high ionic conductivity and has good electrochemical performance. Moreover, the present invention can achieve the purpose of improving air stability without stabilizing the coating layer through a high-temperature sintering process, reducing the processing technology, being more simplified and feasible for practical applications, and greatly reducing the processing cost. In particular, it can coat nanoscale sulfide solid electrolyte particles, which has more practical application value.
[0064] It should be understood that the application of the present invention is not limited to the above examples. For those of ordinary skill in the art, improvements or transformations can be made according to the above description, and all such improvements and transformations should fall within the protection scope of the appended claims of the present invention.
Claims
1. A preparation method of a surface-coated sulfide solid electrolyte, characterized in that, Comprising: Step S1: Mix and stir a sulfide solid electrolyte and a first solvent to obtain a first mixed solution; Mix and stir nanoparticles with oxygen-containing functional groups and a second solvent to obtain a second mixed solution; Step S2: Add the second mixed solution to the first mixed solution and stir to obtain a third mixed solution; Step S3: Vacuum-dry the third mixed solution to obtain the surface-coated sulfide solid electrolyte.
2. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, wherein The nanoparticles with oxygen-containing functional groups are one or more of nano-aluminum oxide, lithium aluminum titanium phosphate nanometer, and lithium phosphate nanometer.
3. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, wherein, The particle size of the sulfide solid electrolyte is 400 nm to 10 μm, and the particle size of the nanoparticles with oxygen-containing functional groups is 5 nm to 10 nm.
4. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, characterized in that, The solid content of the first mixed solution is 10% to 50%, and the solid content of the second mixed solution is 10% to 50%.
5. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, characterized in that, The first solvent and the second solvent are each independently selected from one or more of p-xylene, butyl acetate, and toluene.
6. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, characterized in that, In Step S2, the addition rate of the second mixed solution is 0.5 s / drop to 2 s / drop, and the addition amount of the second mixed solution is 0.25% to 2% of the mass of the first mixed solution.
7. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, characterized in that, In Step S2, the stirring speed is 200 r / min to 2000 r / min, and the stirring time is 5 min to 2 h.
8. The preparation method of the surface-coated sulfide solid electrolyte according to claim 1, characterized in that, The temperature of the vacuum drying is 50°C to 200°C, and the time of the vacuum drying is 10 h to 24 h.
10. A all-solid-state lithium battery, characterized in that, 9. A surface-coated sulfide solid electrolyte prepared by the preparation method of the surface-coated sulfide solid electrolyte according to any one of claims 1 to 8. Comprising the surface-coated sulfide solid electrolyte according to claim 9.
Citation Information
Cited By
Lithium-sulfur-phosphorus-chlorine-bromine solid electrolyte, preparation method thereof and all-solid-state battery
CN121292383A
A lithium-sulfur-phosphorus-chloro-bromine solid electrolyte, its preparation method, and an all-solid-state battery
CN121292383B
Nanoscale sulfide solid electrolyte coated with fluorine-containing lithium salt on surface and preparation method of nanoscale sulfide solid electrolyte
CN122224939A
